Regional Development Planning for The Riam Ensiling Tourism Destination, Sanggau Regency - Harjanti, Diah Trismi; Arini, Audi Cindra; Christanto, Ludovicus Manditya Hari; Tampubolon, Budiman (Universitas Tanjungpura, 2024)
The tourism sector in Indonesia stands out as an important regional income potential, especially for developing countries like Indonesia. The importance of the tourism sector in a social context can be seen from the expansion of employment opportunities and infrastructure development that supports tourism activities. From an economic perspective, the tourism sector contributes to regional income through taxes and foreign exchange obtained from tourists. Sanggau Regency, with its abundant cultural and natural riches, is expected to become a leading tourist destination in the future. This research focuses on the Riam Ensiling tourist destination area in Sanggau Regency, which has been identified as a Tourism Strategic Area. Through this analysis, it is hoped that it will be able to strengthen the implementation of development of tourist destination areas as an integral part of the Tourism Development Area in accordance with the Master Plan for Tourism Development in Sanggau Regency. This research uses qualitative methods to achieve research objectives with SWOT analysis to develop appropriate strategies. The results obtained from this research are that the Development Strategy for the Riam Ensiling Tourist Destination Area can be carried out by 1) Improving the quality of human resources; 2) Procurement of facilities and infrastructure to support tourism activities in Riam Ensiling; 3) Improvement of the facility maintenance system at Riam Ensiling; 4) Promote tourist attractions on social media; 5) Building Brand Image in Riam Ensiling; and 6) Establishing cooperation to procure the management budget for the Riam Ensiling tourist attraction.